No law intellectual property in the image of an absolute First Amendment - Lange, David, 1938-; Powell, Jefferson, 1954- (Stanford, Calif. : Stanford Law Books, 2009)
The original text of the Constitution grants Congress the power to create a regime of intellectual property protection. The First Amendment, however, prohibits Congress from enacting any law that abridges the freedoms of speech and of the press. This book explores the tensions in these two conflicting provisions.
Specialized.
Description based on print version record.
Includes bibliographical references and index.
Keywords: United States; Intellectual property -- United States; Freedom of expression -- United States; Law; United States of America, USA; Laws of specific jurisdictions & specific areas of law; Human rights & civil liberties; Intellectual property law